Condenser Design on Plastic Oil Distillation Equipment - Novarini, N; Kurniawan, Sigit; Rusdianasari, R; Bow, Yohandri; Rifa'i, Ahmad Imam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
The pyrolysis method is a technology in energy conversion that can be applied in processing plastic waste into alternative fuels in liquid form. The pyrolysis method begins with heating the plastic waste in the reactor at a temperature of more than 400°C so that the thermal degradation process of the material occurs without oxygen content, causing a phase change to the vapor phase. The vapor phase is cooled into the condenser to convert it into a liquid phase to obtain liquid fuel from plastic waste. In this study, the pyrolysis condenser design in changing the vapor phase from the reactor to the liquid phase was designed using water as a coolant on the annular side with a coolant inlet temperature of 25 ° C and a coolant outlet temperature of 35°C. The results showed that an annular side dimension with a diameter of 250 mm and a height of 250 mm was needed to reduce the temperature of the inlet condenser fuel vapor from 60°C to 30°C. Furthermore, the inner pipe of the condenser is made of copper material, which is formed by a spiral with a spiral diameter of 250 mm, an inner diameter of 25 mm, and a tubing length of 4,870 mm.